OSCE in action: evaluating clinical skills in phc670 and phc671 - Taridi, Nur Syazwani; Jamludin, Nurul Ashikin; Ismail, Farhana Fakhira; Muda, Mohd Rahimi; Shapri, Nik Aisyah Najwa Nik Mustaffa; Hamdan, Nor Elyzatul Akma; Sha’ari, Mohamad Suhaidi (Faculty of Pharmacy, 2026)
On 6 and 7 January 2026, the Objective Structured Clinical Examination (OSCE) of PHC671 Applied Therapeutics in Infectious Diseases and Malignancies and PHC670 Community Pharmacy courses under the Pharmacy Practice and Clinical Pharmacy Department was successfully conducted. The primary objective of the OSCE was to assess students’ competency in delivering patient-centered pharmaceutical care using the Pharmacists’ Patient Care Process (PPCP) framework. It tested not only knowledge but also essential skills such as clinical reasoning, decision-making, communication, and professionalism, which are critical for safe and effective practice in primary and specialised healthcare settings. ththThe OSCE comprised several stations designed to reflect common and real-life pharmacy practices. These included patient demographic and clinical history taking, prescription and/or medication review, identification of drug-related problems, development of pharmaceutical care plans, and professional documentation. A standardised timing system was used to ensure consistency across all students. To maintain examination integrity, students were placed in a pre-quarantine room before the OSCE commenced and directed to the post- quarantine room upon completion. This structured process prevented information sharing between students and supported an objective assessment of competency.